A Charlie Brown Christmas - Schulz, Charles M. (Charles Monroe), 1922-2000; Testa, Maggie (Peanuts, 2017)
This storybook is based on the Peanuts special, A Charlie Brown Christmas, and features a cloth cover with foil stamping.